The meeting after the meeting: A conceptualization and process model - Meinecke, Annika L.; Handke, Lisa (Organizational Psychology Review, 2022)
This article offers initial theorizing on an understudied phenomenon in the workplace: the meeting after the meeting (MATM). As an informal and unscheduled event, the MATM takes place outside managerial control and has potentially far-reaching consequences. However, our current knowledge of the MATM relies primarily on practitioner observations, and conceptual work that integrates the MATM into the larger meeting science literature is missing. This article fills this gap by outlining key defining features of the MATM that can be used to structure future research. Moreover, and based on theorizing concerning the affect-generating nature of meetings, we develop an affect-based process model that focuses on the antecedents and boundary conditions of the MATM at the episodic level and shines light on meetings as a sequential phenomenon. Plain Language Summary This article sheds light on an understudied but rather common phenomenon in the workplace: The meeting after the meeting (MATM). Defined as an unscheduled, informal and confidential communication event, the MATM has the potential to create new structures in everyday organizational life. Yet, our current knowledge of this particular meeting type is very limited and largely based on anecdotal accounts by practitioners. To guide future research, this article first outlines key features of the MATM, focusing on when the MATM occurs, where it takes place, how it takes place, why it takes place, and who is involved in the MATM. Next, this article presents an affect-based process model of the MATM. To this end, antecedents and boundary conditions at the episodic level are outlined, highlighting that meetings should be seen as interconnected, sequential events.
CRIS-Team Scopus Importer:2023-09-18
Keywords: communication; formal meetings; informal meetings; sensemaking